Development of Guided Discovery Based Stoichiometry E-Modules to Improve Students' Science Literacy - Harnas, Dolla Mulyana; Oktavia, Budhi; Azhar, Minda; Dewata, Indang; Pikoli, Masrid (Jurnal Pendidikan MIPA, 2022)
This research aims to create e-modules based on guided discovery learning that are effective, practical, and support student learning. The research type uses research and development (R&D) using a 4-D model with four steps: definition, design, development, and dissemination. This tool is in the form of a questionnaire on effectiveness and feasibility. Elastic modulus is verified by her 6 validators. Data were analyzed according to the Aikens V formula and percent utility. In the analysis of content validity and technical rating, the average V of Aikens with high valid categories was 0.85 and 0.83. Teacher and student ratings of the practicality questionnaire data were 82% and 83% in the highly practical category. Data analysis shows that young's modulus has high validity and practicality. Therefore, it can be concluded that e-modules based on guided discovery learning are effective, practical, and categorized as teaching materials that improve students' scientific literacy.Keywords: e-module, stoichiometry, guided discovery learning, science literacy.